An Analysis of Cost Efficiency and Loan Loss Provisioning Behaviour in Chinese Commercial Banks - LI, WANYING (2017)
This paper investigates loan loss provisioning (LLP) behaviour by Chinese banks during the period 2011-2015. We test the income-smoothing, capital management, and business cycle hypotheses, in the meanwhile, test whether the cost efficiency has the influence on LLP behaviour. Our results show that Chinese commercial banks have a high level of cost efficiency but it does not affect the LLP behaviour. And there is no evidence that Chinese commercial banks have income smoothing and capital management behaviour, while the results reflect that Chinese commercial banks have pro-cyclical provisioning behaviour. Besides, we find that lagged term of loan loss provisions, total interest income on loans, growth of gross loans and non-performing loans have influences on provisioning behaviour. At last, some advice is proposed on how to mitigate pro-cyclical provisioning behaviour.